Enhancing programmatic scale-up: Applying the consolidated framework for implementation research to evaluate decentralized drug-resistant tuberculosis services in Southern Nigeria - Ngozi Murphy-Okpala; Chinwe Eze; Edmund Ndudi Ossai; Chibuike Innocent Agu; Ifeyinwa Ezenwosu; Charles Nwafor; Ngozi Ekeke; Anthony Meka; Sode Matiku; Beatrice Kirubi; Okechukwu Ezeakile; Martin Njoku; et al. (PLoS ONE, 2025)
Background Decentralization of Drug-Resistant Tuberculosis (DR-TB) services using multilevel interventions was piloted in Akwa-Ibom and Oyo States of Nigeria, which had high rates of pre-treatment loss-to-follow-up in 2021. The varying outcomes of the intervention strategies necessitated understanding what worked well and why. This study aimed to identify enablers and barriers shaping the implementation of decentralized DR-TB services in these states and provide actionable strategies for programmatic scale-up. Methods Semi-structured key informant interviews were conducted with 40 stakeholders involved in the pilot implementation of decentralized DR-TB services in southern Nigeria. Interviews were audio-recorded, transcribed verbatim, and template analysis done using NVivo statistical software, adapting the Consolidated Framework for Implementation Research (CFIR) constructs and sub-constructs as priori codes for data synthesis and analysis. Results The study identified enablers and barriers across the five CFIR domains. Intervention characteristics facilitators stemmed from its relative advantage and design enabling faster notification of diagnosed DR-TB patients, enhanced patient tracking, ease of conducting baseline investigations, bringing treatment closer by reducing transportation challenges, unique role of the Volunteer Liaison Officer, utility of WhatsApp platform, private sector engagement, and DR-TB survivors as peer counsellors. Critical incidents such as the removal of fuel subsidies and economic difficulties; and inner setting factors like existing infrastructure and health workforce, culture, available resources and tension for change from high pre-treatment loss to follow-up, and intervention’s alignment with workflow; all facilitated implementation. Barriers identified included: challenges with verbal autopsy, low adoption of Unstructured Supplementary Service Data (USSD) innovation, pricing of baseline tests, poor power supply, inadequate laboratory facilities and insufficient DR-TB expertise in rural areas, and fear of TB infection among health workers. Conclusion The findings demonstrate the ease of implementing decentralized DR-TB services and their advantages over a centralized approach. Key enablers centered on innovation and individual characteristics, and inner setting dynamics within the TB program. There were more facilitators than barriers, with most barriers being modifiable despite some outer setting factors like fiscal policy and geographic access. These insights can guide nationwide adoption and scale-up of decentralized DR-TB services in Nigeria and similar settings in low-and middle-income countries. Trial Registration Pan African Clinical Trial Registry PACTR202309676675265